ANALISIS FUNGSI MANAJEMEN BIDAN KOORDINATOR PUSKESMAS DALAM PELAKSANAAN PROGRAM ASI EKSKLUSIF DI KABUPATEN MAGELANG - Riski Malimpa; Ayun Sriatmi; Putri Asmita Wigati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Infant and children mortality caused by infectious disease can be prevented with exclusive breastfeeding among 6 month. The Government has made the regulation and program to support exclusive breastfeeding implementation. But in the reality, trend of exclusive breastfeeding in Magelang from 2010 until 2012 has fluctuative condition that are 10,9%; 9,79%; and 11,72% still low from the target which is 80%. Exclusive breastfeeding achievement is not far from the managerial skill of the midwife in Public Health Center. The goal of research is to analyse the Midwife Coordinator’s management function on Public Health Center at breastfeeding program in Magelang. This is a qualitative research use descriptive method. Data collected from indepth interview uses question role. Subject of research are 15 people that consist of 6 Midwife Coordinator in 6 Public Health Center as Mayor informan, and 6 Midwife in 6 Public Health Center, 1 people of Kasie. Kesga Dinkes, also 2 people breastfeeding mother as triangulation informant. Subjects of the research put by purposive method that are from 3 Public Health Center with highest level of exclusive breastfeeding and 3 Public Health Center with lowest level of exclusive breastfeeding average among 3 years. Data analysis use content analyse. Output of the research shows that planning, organizing, actuating, and controlling by Midwifes Coordinator are not optimal. Suggestions for Midwifes Coordinator are making activity plan/plan of action for breastfeeding program, staffing the program, increasing its cooperation with professional organizations, and implementing interventions pattern.